ANALYSIS OF POTENTIALITIES AND CHALLENGES FOR DEVELOPING TOURISM IN PRESIDENTE EPITACIO-SP AND THE IMPLICATIONS IN THE USE OF WATER RESOURCES - Oliveira, Suelen Daianne [UNESP]; Tommaselli, Jose Tadeu Garcia [UNESP]; Granado, Danielli Cristina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2021)
The reservoirs of hydroelectric power plants are artificial ecosystems of great importance providing multiple uses, even for tourism. The tourist activity in the HPP reservoir Engineer Sergio Motta, installed in the district of Primavera, municipality of Rosana-SP, enables job creation and has been conductive to local development for the municipality of Presidente Epitacio-SP. However, without adequate planning and continuous monitoring, there is a high probability that tourism will cause significant negative impacts, which may compromise the quality of water resources and affect the activities in the reservoir in the long term, mainly fishing and bathing. This article aims at analyzing tourism development, regarding the connection of tourist activity and water resources in the municipality. As methodological procedure, a bibliographical and documentary survey was carried out, in conjunction with interviews of municipal government representatives and local entrepreneurs. The reservoir is appointed in the interviews as the prime motivator of tourism activity. The water body might be affected by tourism owing to occupations on the banks of the reservoir in which most places, have no sewage collection and treatment systems, as well as on tourist spots. It is worth mentioning the possible consequences that may be caused on fisheries due to predation and the amount of waste engendered by the activity, which becomes a risk factor to water body as a result of inefficient cleaning services. It shall be understood that local management and entrepreneurs must bear in mind that water resources degradation is harmful for tourism, as this is the city's main attraction.
Keywords: Tourism; Planning; Presidente Epitacio